Treatment of invasive fungal infections in intensive care units with micafungin: The MYRIADE study. Issue 5 (25th February 2020) - Timsit, Jean‐François; Leverger, Guy; Milpied, Noël; Gachot, Bertrand
Summary: Background: Invasive fungal infections (IFIs) contribute significantly to nosocomial illness in intensive care units (ICUs). Current practice guidelines recommend echinocandins, such as micafungin, for the treatment of invasive candidiasis. However, limited information on their use in real‐world practice is available. Objective: To describe the conditions of the use of micafungin in daily clinical practice and to evaluate its effectiveness and tolerability under real‐world conditions. Patients/Methods: This observational, prospective, multicentre study was performed in 34 ICUs in France. The study population consisted of 275 patients ≥16 years old who received treatment with micafungin during the inclusion period. Dose and duration of treatment were at the discretion of the physician. Results: Proven invasive candidiasis was documented before treatment in 106 patients (38.6%); 263 patients (95.6%) received the recommended dose (100 mg/day); 78 patients (28.8%) were treated for the recommended duration. A successful outcome was observed for 217 patients (79.2%). This proportion was significantly higher (83.3%; P < .0001) in patients treated for ≥14 days. Three patients discontinued treatment due to an adverse event considered related to micafungin. No clear impact of micafungin on hepatic function was observed. Conclusion: Micafungin was effective in >75% of patients treated for IFIs in ICUs in France; outcomes may be improved with closer adherence to the recommended treatment duration.